Mapping global trends in adipose-derived mesenchymal stem cell research: A bibliometric analysis using scopus database. (May 2022) - Sharun, Khan; Musa, Taha Hussein; Musa, Hassan Hussein; Kumar, Rohit; Pawde, A.M.; Chandra, Vikash; Tuli, Hardeep Singh; Dhama, Kuldeep; Amarpal; Sharma, G. Taru
Abstract: Background and objective: Adipose-derived mesenchymal stem cells (AdMSC) are multipotent adult mesenchymal cells isolated and cultured from the stromal vascular fraction derived from adipose tissue. The present study was conducted to analyze the global trends in AdMSC research using bibliometric and visual analysis tools. Methods: The literature search was done on February 13, 2022, using appropriate keywords and inclusion-exclusion criteria from the Scopus database. The extracted data were retrospectively analyzed and visualized using Bibliometrics and R packages and VOSviewer. Results: Preliminary analysis identified 1569 documents from the Scopus database published between 2005 and 2021. The average citations received per document was 26.51, whereas the average citations per year per document was 3.347. In addition, the selected documents had an h -index value of 90. China was the most productive country, whereas Seoul National University (South Korea) was identified as the most productive institute/university in AdMSC research. In addition, the National Natural Science Foundation of China funded the most research studies in AdMSC research. Conclusion: The findings from this study indicate a progressive increase in interest among the research community towards AdMSC, suggesting promising prospects in the coming years.